Contemporary Indian English literature contexts – authors – genres – model analyses - Sandten, Cecile 1966-; Karmakar, Indrani; Knebel Doeberitz, Oliver von 1975-2023 (Narr Francke Attempto, 2024)
"Contemporary Indian English Literature focuses on the recent history of Indian literature in English since the publication of Salman Rushdie's novel Midnight's Children (1981), a watershed moment for Indian writing in English in the global literary landscape. The chapters in this volume consider a wide range of poets, novelists, short fiction writers and dramatists who have notably contributed to the proliferation of Indian literature in English from the late 20th century to the present. The volume provides an introduction to current developments in Indian English literature and explains general ideas, as well as the specific features and styles of selected writers from this wide spectrum. It addresses students working in this field at university level, and includes thorough reading lists and study questions to encourage students to read, reflect on and write about Indian English literature critically."
Keywords: Geschichte 1981-2024; Geschichte 1981-2022; Indianer; Englisch; Literatur; USA; Indien; Abhishek Majumdar; Amit Chaudhuri; Anglophone Indian Fiction; Annie Zaidi; Anuradha Roy; Aravind Adiga; Arundhati Roy; Ausbeutung; Chutnificatio; Contemporary Indian English Drama; Demokrati; Der weibliche Körper; Diaspora; Exit West; Female Body; Female Identities; Feminismus; Final Solutions; Literaturwissenschaft, allgemein; Aufsatzsammlung